1988
DOI: 10.1016/0014-5793(88)80834-2
|View full text |Cite
|
Sign up to set email alerts
|

Yeast iso‐l‐cytochrome c: Genetic analysis of structural requirements

Abstract: We describe the use of classical and molecular genetic techniques to investigate the folding, stability, and enzymatic requirements of iso‐l‐cytochrome c from the yeast Saccharomyces cerevisiae. Interpretation of the defects associated with an extensive series of altered forms of iso‐l‐cytochrome c was facilitated by the recently resolved three dimensional structure of iso‐l‐cytochrome c [(1987) J. Mol. Biol. 199, 295–314], and by comparison with the phylogenetic series of eukaryotic cytochromes c. Residue rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…Mutant yeast and Neurospora strains have been isolated that lack holocytochrome c in vivo because of a deficiency in heme lyase (9,28) or because they contain altered forms of cytochrome c with amino acid substitutions at the site of covalent heme attachment (17). However, the instability of the apo form of iso-1-cytochrome c, the predominant isozyme in S. cerevisiae (11), or of the only apocytochrome c in N. crassa (28) made it difficult to determine whether the defect in heme attachment also resulted in a defect in import.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant yeast and Neurospora strains have been isolated that lack holocytochrome c in vivo because of a deficiency in heme lyase (9,28) or because they contain altered forms of cytochrome c with amino acid substitutions at the site of covalent heme attachment (17). However, the instability of the apo form of iso-1-cytochrome c, the predominant isozyme in S. cerevisiae (11), or of the only apocytochrome c in N. crassa (28) made it difficult to determine whether the defect in heme attachment also resulted in a defect in import.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, numerous mutations have been introduced into codons for conserved amino acids in cytochrome c sequences (for reviews see Mauk, 1991 ;Hampsey et al, 1988). One of the conclusions of this work is that certain amino acids can functionally replace evolutionarily invariant residues, sometimes at activity levels indistinguishable from wild type, indicating that evolutionary invariance does not necessarily imply functional invariance.…”
mentioning
confidence: 91%
“…for [Ile57]Cyt-SCH3 (8.0 kcal/mol), given in Table 2, is over (15,25) reported that replacement of Gly-34 in iso-1-cytochrome c with Ser, Asn, or Asp caused instability in vitro, as inferred from lability during extractions, and caused diminished function in vivo, as measured by less growth in lactate medium. The loss of function by the replacements of Gly-34 was attributed to the inability of the protein to accommodate a side chain larger than the glycine proton, thereby altering the bond angles at position 34 (15,25).…”
mentioning
confidence: 99%
“…The loss of function by the replacements of Gly-34 was attributed to the inability of the protein to accommodate a side chain larger than the glycine proton, thereby altering the bond angles at position 34 (15,25). Similarly, iso-1-cytochromes c are functional with the The forces which stabilize proteins act simultaneously on every residue, resulting in a small net stabilization.…”
mentioning
confidence: 99%